El periódico que llegó a la vida nacional. Los primeros años del diario Excelsior (1916-1932) - Burkholder de la Rosa, Arno (El Colegio de México, A.C., 2009)
This work covers the history of the Mexican newspaper  Excelsior between  1916 and 1932. The author  examines the context in which  the newspaper  was born  —triumph of Constitutionalism and conflicts  between  its constituting groups—  and  the survival and  strengthening of  business  journalism,  which  was born during the Porfiriato and now had to negotiate with revolutionary leaders. Excelsior maintained  during its first stage a “moderately conservative” editorial line, which  brought about trouble with the governments of Álvaro Obregón and Plutarco Elías Calles, but which also led to a growing prestige among its readers —urban middle— and high —class in the capital and other cities. This period ended when the newspaper failed to overcome its problems with the revolutionary regimes and had to face a deep economic crisis leading to bankruptcy.